Úttörő innovációk az emberiség történetében - Az innováció múltja és jelene - Kuller Dóra (2019)
The purpose of my examination paper is to study how innovations affected human civili-zation from the beginning of the first industrial revolution up to the present day, which is ca. 300 years. The theory is, that the most determinative innovations had not only influenced the nar-rowly defined economic environment. They accomplished more,than simply creating new markets, helping to raise new companies or put already existing companies in a monopoly situation. Their effects go beyond. Innovations were starting points of in-depth changes, which left their marks directly or indirectly on all aspects of life. As a result, previously non exsistent industries were created and already existing industries had been proposed a new beginning. Therefore, the economic and social processes had gotten into a brand new channel. In the opinion of researchers, humankind is facing big changes again (even big-ger than ever before), which makes the historic overview particularly relevant. These changes are the fourth industrial revolution or the so called industry 4.0. The examination paper analyses these changes in the context of innovation theories. The thesis is a result of secondary research, which relies not just on hungarian academic li-terature, but (especially the parts about industry 4.0.) on foreign language sources. This is caused by the novelty of the theme, since it is aboutcurrent processes, not yet established inventions and resulting innovations. Because of this the available sources mainly rely on hypotethical analysis. By describing the concept and theoretical models of innovation, the examination paper provides the basis to analyse concrete innovations on predetermined criterias. The thesis – separately for historical periods - analyses determinative innovations, which were the cor-nertones of radical changes. It provides more detailed insight into these transitions, with describing each period’s changes in economy, society and lifestyle. The examination paper states, that the innovations in the industrial revolutions not only influenced the society and lifestyle through economical changes (for example the inno-vations, which caused the rise of textile industry), but how innovations could influence everyday life directly (for example the spread of the internet). Although the transition is a development in long-term historical perspective, it did not exclusively have positive and immediate effects. A good example for this is the urbanization caused by the economical development in the XIX. century – the bus of which; masses of people’s living condition got worse. This justifies the providence, as we study the effects of the fourth industrial re-volution, and necessitates to be aware of the potential negative consequences, because it could help to prepare and prevent these problems.